2012
DOI: 10.1063/1.4731717
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring coercivity of unbiased exchange-coupled ferromagnet/antiferromagnet bilayers

Abstract: Spin-glass-like freezing in spin-chain compounds Ca3Co2−xMnxO6: Effect of disorder J. Appl. Phys. 112, 103923 (2012) Magnetoelectric coupling in La0.6Ca0.4MnO3-Bi0.6Nd0.4TiO3 composite thin films derived by a chemical solution deposition method Appl. Phys. Lett. 101, 212902 (2012) Areal density limitation in bit-patterned, heat-assisted magnetic recording using FePtX media J. Appl. Phys. 112, 093920 (2012) Hard ferromagnetism in melt-spun Hf2Co11B alloys Appl. Phys. Lett. 101, 202401 (2012) Electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…The direct exchange interaction between the core and shell spins was prevented by the It is interesting that numerous research studies revealed the occurrence of (unconventional) EB. For example, unconventional EB with T N > T C has been observed in some systems such as core-shell nanoparticles and thin-film heterostructures [41][42][43][44]. In addition, EB was reported to occur in systems cooled from temperatures below T N [45].…”
Section: Magnetic Measurements Of the S1 And S2 Core-shell Nanoparticlesmentioning
confidence: 99%
“…The direct exchange interaction between the core and shell spins was prevented by the It is interesting that numerous research studies revealed the occurrence of (unconventional) EB. For example, unconventional EB with T N > T C has been observed in some systems such as core-shell nanoparticles and thin-film heterostructures [41][42][43][44]. In addition, EB was reported to occur in systems cooled from temperatures below T N [45].…”
Section: Magnetic Measurements Of the S1 And S2 Core-shell Nanoparticlesmentioning
confidence: 99%
“…In conventional EB systems with T C > T N , bias is obtained after either applying strong magnetic field during the samples' production or at temperatures lower than T N [29,30], or by post-annealing or ion bombardment [31][32][33][34] in the presence of magnetic field; even the remnant magnetization of the FM acquired prior cooling can lead to shifted magnetization curves [35]. Although certain post-deposition anneals or ion irradiations significantly enhanced H C , none of these treatments has been able to induce EB in our exchange-coupled IrMn/NiCu system [16].…”
Section: Methodsmentioning
confidence: 83%
“…Pieces of the as-made films have been subjected to 40 keV irradiation with He or Ge ions at different fluences. Details on the samples' deposition, their structural characterization and ion irradiation can be found in a previous work of ours [16]. In conventional EB systems with T C > T N , bias is obtained after either applying strong magnetic field during the samples' production or at temperatures lower than T N [29,30], or by post-annealing or ion bombardment [31][32][33][34] in the presence of magnetic field; even the remnant magnetization of the FM acquired prior cooling can lead to shifted magnetization curves [35].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…fase majoritariamente FM. O maior campo coercivo obtido em baixas temperaturas se dá por se tratar de uma amostra heterogênia, onde há uma distribuição de direções nas quais ocorrem o acoplamento entre as fases FM (metaestável) e AFM, resultando num incremento do campo coercivo[59,60], diferentemente de acoplamentos altamente orientados que resultam no fenômeno de exchange-bias[61,62].Analisando os valores de campo coercivo para as medidas feitas de maneira perpendicular ao plano do filme, estes aumentam com o incremento da temperatura, sendo observado este comportamento tanto para os nanofios de Ni como para as amostras S500 e S600tt, porém, quando o filme não está na presença de nanofios de Ni ocorre uma diminuição do campo coercivo, do mesmo modo que nas medidas paralelas ao plano do filme. O incremento do campo coercivo já foi relatado em nanofios de Ni, como apresentado nafig.…”
unclassified